Dietary protein content for an optimal diet: a clinical view. Issue 3 (25th April 2017) - Santarpia, Lidia; Contaldo, Franco; Pasanisi, Fabrizio
Abstract: The dietary protein role in different clinical nutritional conditions and some physio‐pathological perspectives is a current and hot topic to discuss. Recent Proceedings of the Protein Summit 2, joining more than 60 nutrition scientists, health experts, and nutrition educators, suggest to increase plant but, in particular, animal protein intake because richer in leucine and consequently more effective to influence anabolic protein metabolism. The Panel conclusions are in apparent contradiction with the nutritional ecology statements, which strongly sustain the reduction of animal origin foods in the human diet and are currently concerned about the excessive, mainly animal protein intake in western and westernized Countries. In conclusion, it is time to carefully evaluate protein and aminoacid intake accurately considering quality, digestibility, daily distribution and individual characteristics.